2004
DOI: 10.1016/j.ast.2003.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and prediction of emissions of aerosols and gaseous precursors from gas turbine engines (PartEmis): an overview

Abstract: An overview of the goals and achievements of the European PartEmis project (Measurement and prediction of emissions of aerosols and gaseous precursors from gas turbine engines) is discussed in this paper. PartEmis is focussed on the characterisation and quantification of exhaust emissions from a gas turbine engine. The engine was composed of a combustor and a unit to simulate a 3-shaft turbine section (so-called Hot End Simulator; HES). A comprehensive suite of aerosol, gas and chemi-ion measurements were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 29 publications
1
28
0
Order By: Relevance
“…Kittelson et al [11] measured charged soot particles in diesel engine exhaust and explored the possibility of removing them using electrostatic precipitation. Wilson et al [12] have identified high concentrations of small charged soot particles in the exhaust of a gas turbine aircraft engine, which Sorokin and Arnold [13] have achieved modest success in modeling. Clearly, studying the formation and dynamics of charged soot particles can play an important role in practical issues of controlling and measuring soot emissions.…”
Section: Introductionmentioning
confidence: 98%
“…Kittelson et al [11] measured charged soot particles in diesel engine exhaust and explored the possibility of removing them using electrostatic precipitation. Wilson et al [12] have identified high concentrations of small charged soot particles in the exhaust of a gas turbine aircraft engine, which Sorokin and Arnold [13] have achieved modest success in modeling. Clearly, studying the formation and dynamics of charged soot particles can play an important role in practical issues of controlling and measuring soot emissions.…”
Section: Introductionmentioning
confidence: 98%
“…Specific open issues relating to aircraft particulate emissions include the quantification of particles that are emitted on the ground at airports and at altitude during flights and an understanding of the role of emitted aerosol precursors in particle nucleation, growth, and particle activation [10]. Relatively little is known about the chemical speciation and sources (e.g., contributions of lubricating oils to volatile particulate matter [10]) of the emissions of particles and aerosol precursor gases from aircraft engines, and so a number of recent studies [e.g., Atmospheric Effects of Aviation Project study, Experiment to Characterize Aircraft Volatile Aerosol and Trace Species Emissions (EXCAVATE), NASA/QinetiQ, PartEmis (measurement and predictions of the emission of aerosols and gaseous precursors from gas turbine engines), have been directed at improving understanding of these emissions and how they may contribute to particles in the atmosphere [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A brief description of the combustor and test-rig used during PartEmis, is given below, and further details can be found in Wilson et al (2004). A turbo-annular, transpiration cooled combustor was used for tests on QinetiQ's High Pressure Combustion Rig at Farnborough, UK.…”
Section: Experimental Setup and Sampling Systemmentioning
confidence: 99%